Management of gingival polyp in restoration procedure: A case report - Bambang T. Hartomo; Fanni K. Djati; Rosita Anggraeni (Journal of Dentomaxillofacial Science, 2021)
Objective: Gingival Polyp, which are focal fibrous hyperplastic lesion, are also known as, localized gingival enlargement. represent a reactive hyperplasia of fibrous connective tissue in response of trauma or irritation. The gold standard for its treatment is surgical excision performed with a scalpel, electrocautery or lasers. This case report presents treatment for proximal carious teeth with gingival polyp. Methods: A 20 year male patient reported to Conservative Department. He complained of proximal cavity, mild sensitivity to cold, painless growth of the gum in lower right back tooth region. An oral examination revealed a reddish- pink soft gingival overgrowth of 5x4 mm in size, localized to interproximal area and presenting with a pedunculated base with relation to teeth 45. Summating the clinical presenting features, a provisional clinical diagnosis of gingival polyp was made. Results: First treatment was caries cleansing, then the cavity was closed with cotton with dripped of eugenol. The gingival polyp are smaller than before. Then a local anesthetic is performed to remove the remaining gingival polyp tissue. Gingival polyp are cut using an excavator and restoration cavity using composite Conclusion: Eugenol exerts a beneficial action on anti-inflammatory so could reduce the edema of gingival soft tisuue. The treatment acceptance but the expected results are still not maximal so that it still needs to excision.